Examining an endogenous modulator of chaperone‐mediated autophagy in neurons across Braak stages of Alzheimer's disease. (20th December 2022) - Weickhardt, Alexander F.; Lee, Yoo Bin; Piergies, Antonia M. H.; Li, Song; Lew, Caroline; McCabe, Mericka; Bourdenx, Mathieu; Scrivo, Aurora; Gavathiotis, Evripidis; Cuervo, Ana Maria; Grinberg, Lea Tenenholz
Abstract: Background: Defective clearance of tau by neuronal autophagy has been implicated in the accumulation of toxic forms of tau in Alzheimer's disease (AD). A novel, endogenous activator of chaperone‐mediated autophagy (CMA‐modulator) was identified in cell culture experiments (Cuervo laboratory, unpublished data). It is unclear what role this endogenous CMA‐modulator plays in AD. We hypothesized that loss of the CMA‐modulator in neurons could lead to decreased clearance of abnormal tau monomers, promoting the accumulation of toxic forms of tau. This study examined the proportion of neurons with CMA‐modulator in postmortem brain tissue from subjects with a range of AD neuropathologic changes as well as both amnestic and non‐amnestic AD presentation. Method: We used multiplex immunofluorescence (CMA‐modulator, NeuN for neurons, 1F3C for acetyl‐tau, AT100 for phospho‐tau) on tissue microarrays in the inferior temporal gyrus of 17 subjects (Table 1) and for each subject quantified neurons within a gray matter area of 7.4 ‐ 7.6 mm 2 using digital pathology. To analyze the change in percentage of neurons positive for CMA‐modulator across Braak stages, we fit a linear regression model. Result: In amnestic AD, the percentage of neurons positive for CMA‐modulator declined linearly with advancing Braak stage, but this trend was not statistically significant (slope = 2.42% loss per Braak stage, p = 0.086). The predicted percentage of positive neurons was 22.8% at Braak stage 0 and 8.25% at Braak stage 6 and amnestic presentation. All non‐amnestic cases were Braak stage 6, and the proportion of neurons positive for the CMA‐modulator varied greatly from 0.2% to 77.1%. There was no significant association between the percentage of CMA‐modulator positive neurons and either age or gender. Quantification for the acetyl‐tau and phospho‐tau markers is ongoing. Conclusion: There may be a gradual loss of the endogenous CMA‐modulator across Braak stages in amnestic AD, but this study was underpowered to draw definitive conclusions. We are increasing the sample size.